The construction and testing of an acoustic energy harvester consisting of a Helmholtz resonator and a loudspeaker - Ikhsan Setiawan; Mulaiyinatus Sifa (Universitas Sebelas Maret, 2020)
Sound energy is all around but not properly utilized despite being a source of electricity. This research was conducted to construct and test an acoustic energy harvester consisting of a Helmholtz resonator and a loudspeaker. The resonator cavity was made of 10 mm-thick cube-shaped acrylic plates with an inner side length of 300 mm while its neck was made of PVC (polyvinyl chloride) pipes with an inner diameter of 55 mm and three length variations at 50 mm, 70 mm, and 90 mm. A 6-inch subwoofer loudspeaker was mounted on the resonator back wall facing the cavity with its terminals connected to a 100-ohm load resistor. The sound waves entering the resonator cavity through the neck were converted into the alternating electric current flowing through the resistor. The test was conducted experimentally by exposing the harvester to sound waves at a maximum sound pressure level (SPL) of 100 dB and frequency variations from 25 Hz to 200 Hz. The root-mean-square (rms) voltages across the resistor were measured to calculate the output rms values for electric power. The results showed seven spectrum peaks which appeared at frequencies of 31 Hz, 37 Hz, 41 Hz, 49 Hz, 58 Hz, 73 Hz, and 82 Hz. Moreover, a shorter neck was also observed to have produced higher output power as indicated by the highest value of 2.75 mW obtained by using a 50 mm-long resonator neck at 37 Hz frequency and 100 dB SPL. These findings showed the acoustic energy harvester used to be effective due to its ability to produce electricity even at low frequencies below 100 Hz.